2001
DOI: 10.1128/cmr.14.4.810-820.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Cerebral Malaria: Recent Experimental Data and Possible Applications for Humans

Abstract: Malaria still is a major public health problem, partly because the pathogenesis of its major complication, cerebral malaria, remains incompletely understood. Experimental models represent useful tools to better understand the mechanisms of this syndrome. Here, data generated by several models are reviewed both in vivo and in vitro; we propose that some pathogenic mechanisms, drawn from data obtained from experiments in a mouse model, may be instrumental in humans. In particular, tumor necrosis factor (TNF) rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
189
0
8

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(201 citation statements)
references
References 104 publications
4
189
0
8
Order By: Relevance
“…This is primarily due to parasite sequestration to the brain EC. Activation of EC is known to be influenced by levels of circulating cytokines such as TNF and IFN-␥ (29), two cytokines in which production is strongly induced by the malaria parasite (5,30). Activated EC can ingest parasite material (31) which could be presented via MHC class I and II molecules often seen to be upregulated during the infection (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is primarily due to parasite sequestration to the brain EC. Activation of EC is known to be influenced by levels of circulating cytokines such as TNF and IFN-␥ (29), two cytokines in which production is strongly induced by the malaria parasite (5,30). Activated EC can ingest parasite material (31) which could be presented via MHC class I and II molecules often seen to be upregulated during the infection (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Studies aimed at assessing the role of leukocytes in the pathogenesis of CM would require sequential sampling of brain tissues, which is clearly unethical in humans. Although no animal model reproduces all the features of human CM, mouse models have been highly informative in studies of CM pathogenesis (5). A systemic role for leukocytes has been deduced in a number of experimental CM studies and some subsets were identified as important (6 -8).…”
mentioning
confidence: 99%
“…Mice received intraperitoneal injections of 1 ϫ 10 6 red blood cells infected with P. berghei ANKA (PbA) (11). The cerebral syndrome (i.e., ataxia and convulsions, rapidly followed by death) occurred on days 7-8 after infection.…”
Section: Infection Of Mice and Treatmentmentioning
confidence: 99%
“…Susceptible strains of mice infected with PbA develop neurological manifestations rapidly followed by death. The pathology is due not to the direct action of the parasite but to a deleterious immune response of the infected host, involving cerebral vascular inflammation with microcirculatory dysfunction (9)(10)(11)(12)(13). The ultimate consequence is disruption of the brain microvasculature, enhancement of blood-brain barrier (BBB) permeability, and edema formation leading to major hemodynamic dysfunction (14)(15)(16).…”
mentioning
confidence: 99%
“…In addition to the fact that 40% of the world population living in tropical and subtropical areas is at risk of contracting the disease, it is estimated that between 300 and 500 million new cases per year will appear, causing 1.5 to 2.7 million deaths annually, striking mostly children under five years old 18,23 .…”
Section: Introductionmentioning
confidence: 99%